2023
DOI: 10.1111/jpm.12970
|View full text |Cite
|
Sign up to set email alerts
|

Community‐based art groups in mental health recovery: A systematic review and narrative synthesis

Jessica Marian Goodman‐Casanova,
Jose Guzman‐Parra,
Fermin Mayoral‐Cleries
et al.

Abstract: IntroductionThough the evidence of the role of the arts in mental health is growing, no systematic review has focused on the impact of art groups in non‐clinical settings in the process of recovery following the CHIME framework.AimThe aim of this study was to examine the effects of engaging in community‐based art groups in mental health recovery.MethodA search in five electronic databases for relevant research using quantitative, qualitative or mixed methods published between 2000 and 2019 identified nine elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In addition, prior studies have supported the efficacy of art therapy in reducing anxiety symptoms in female cancer patients [ 69 ]. Furthermore, reports have indicated that the majority of art therapists are female [ 70 ], and that females are often the predominant users of art therapy [ 71 ]. Therefore, female patients with schizophrenia may be more responsive to visual art therapies, a factor warranting further investigation in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prior studies have supported the efficacy of art therapy in reducing anxiety symptoms in female cancer patients [ 69 ]. Furthermore, reports have indicated that the majority of art therapists are female [ 70 ], and that females are often the predominant users of art therapy [ 71 ]. Therefore, female patients with schizophrenia may be more responsive to visual art therapies, a factor warranting further investigation in future studies.…”
Section: Discussionmentioning
confidence: 99%